Potential Maximization and Coalition Government Formation - Rod Garratt; Cheng-Zhong Qin; James E. Parco; Amnon Rapoport (Fondazione Eni Enrico Mattei (FEEM), 2004)
A model of coalition government formation is presented in which inefficient, non-minimal winning coalitions may form in Nash equilibrium. Predictions for five games are presented and tested experimentally. The experimental data support potential maximization as a refinement of Nash equilibrium. In particular, the data support the prediction that non-minimal winning coalitions occur when the distance between policy positions of the parties is small relative to the value of forming the government. These conditions hold in games 1, 3, 4 and 5, where subjects played their unique potential-maximizing strategies 91, 52, 82 and 84 percent of the time, respectively. In the remaining game (Game 2) experimental data support the prediction of a minimal winning coalition. Players A and B played their unique potential-maximizing strategies 84 and 86 percent of the time, respectively, and the predicted minimal-winning government formed 92 percent of the time (all strategy choices for player C conform with potential maximization in Game 2). In Games 1, 2, 4 and 5 over 98 percent of the observed Nash equilibrium outcomes were those predicted by potential maximization. Other solution concepts including iterated elimination of dominated strategies and strong/coalition proof Nash equilibrium are also tested.
Keywords: C72; C78; D72; 330; Coalition formation; Potential maximization; Nash equilibrium refinements; Experimental study; Minimal winning; Regierungskoalition; Nash-Gleichgewicht; Test; Regierungswechsel